Legal Consequences for Health Workers who Exceed Authority in Medical Services - Sumartini Dewi; Sri Setiawati; Juhari (Universitas Muhammadiyah Palu, 2025)
This article examines the legal implications that healthcare professionals may encounter when they overstep their authorized scope in delivering medical services. Such occurrences are relatively common in Indonesia’s healthcare system, where doctors, nurses, and other medical personnel often act beyond their prescribed authority. Various factors, including lack of awareness, insufficient training, and the pressure to complete tasks quickly, may contribute to these actions. The purpose of this paper is to analyze the legal repercussions for healthcare professionals who exceed their authority and to provide a deeper understanding of the regulations governing the professional authority of healthcare providers in Indonesia. It is hoped that this article will offer valuable insights and enhance healthcare professionals’ understanding of the importance of adhering to legal guidelines in medical practice.